ChIP-Seq in Candida albicans - Sadri Znaidi; Caroline PROUX; Sandra Weber; Simon Drouin; François Robert; Martine Raymond; Jean-Yves Coppée; Christophe d'Enfert (Bio-Protocol, 2014)
Systems biology approaches can be used to study the regulatory interactions occurring between many components of the biological system at the whole-genome level and decipher the circuitries implicated in the regulation of cellular processes, including those imparting virulence to opportunistic fungi. Candida albicans (C. albicans) is a leading human fungal pathogen. It undergoes morphological switching between a budding yeast form and an elongated multicellular hyphal form. This transition is required for C. albicans’ ability to cause disease and is regulated through highly interconnected regulatory interactions between transcription factors (TFs) and target genes. The chromatin immunoprecipitation (ChIP)-High-throughput sequencing (Seq) technology (ChIP-Seq) is a powerful approach for decoding transcriptional regulatory networks. This protocol was optimized for the preparation of ChIP DNA from filamenting C. albicans cells followed by high-throughput sequencing to identify the targets of TFs that regulate the yeast-to-hyphae transition.